Promotion of soft skills in university students through teaching practices: validation of an instrument - Islas-Torres, Claudia (2024)
Currently, in various fields, the demonstration of soft skills by individuals is highly valued, which is why university training processes must aim to enhance these skills among students. In this regard, a cross-sectional analytical study was developed under a holistic approach, aiming to analyze the alignment between university teaching practices and the promotion of students' soft skills. A survey-type instrument was created to capture students' perceptions regarding this relationship. The validation process of the instrument, which was completed by 1,677 participants from various undergraduate programs at a university center in western Mexico, is presented. The content validity index obtained from expert judges was 0.837, while Cronbach's alpha was 0.907. Bartlett’s test of sphericity and the Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy were applied for exploratory factor analysis, resulting in a p-value of 0.001 and a global KMO of 0.957, indicating that the data were optimal. The analysis confirmed the grouping of five factors represented in the operationalization synergies. As a result, adjustments were made to the items, discarding those with a factor loading below 0.5 for not providing significant information to the instrument. This led to a reconfiguration, reducing the total items from 44 to 23, which measure the construct defined in the study in greater depth.